The Influence of E-Recruitment on Employee Performance - Rahma Yuanita Hapsari; Qristin Violinda; M Fadjar Darmaputra (Journal of Islamic Entrepreneurship and Business Research, 2024)
E-recruitment plays a crucial role in companies by enhancing the recruitment process and improving employee performance. Proper recruitment through e-recruitment systems enables organizations to acquire optimal human resources (HR). By sorting and selecting candidates based on specific criteria such as education, experience, or skills, e-recruitment allows companies to adapt quickly to their needs and ensure that new hires possess the required qualifications. This study investigates the impact of e-recruitment on employee performance using SMART-PLS version 3 for data analysis. The sampling method employed was disproportionate stratified random sampling, with 100 respondents participating in the research. Despite its potential, the findings revealed that e-recruitment does not significantly influence employee performance, as indicated by a P-value of 0.228 and a path coefficient of 0.086. The study highlights the importance of aligning recruitment strategies with broader performance objectives while considering other factors that might contribute to employee performance. Although e-recruitment facilitates efficiency in candidate selection, its direct impact on performance requires further exploration, particularly in identifying mediating factors that could strengthen this relationship. These findings provide valuable insights for organizations to refine their recruitment processes, emphasizing the need for a holistic approach that integrates e-recruitment with other performance-enhancing initiatives. Future research could explore the interaction between e-recruitment and factors such as training, motivation, or organizational culture to determine their combined effects on performance outcomes. Thus, while e-recruitment optimizes candidate selection, its role in driving performance may depend on broader organizational practices.